Information Systems Research in Australia and New Zealand: A Survey of Research Activity from 2020 to 2022 - Marc Adam; Sultana Lubna Alam (Australasian Journal of Information Systems)
Over the past 60 years, the information systems (IS) discipline has become an established research field in Australia and New Zealand. Throughout its history, the discipline has experienced an ongoing formation and evolution of its unique identity, with important links to both business and computing-focused research. As a sociotechnical discipline, IS research considers a wide range of phenomena that emerge when social systems interact with technical systems. Yet, there is a lack of research into how recent socioeconomic and technical developments, such as accelerated digitisation in the aftermath of Covid19, widescale university restructuring, and a revision of the government’s research classification schemes, have affected the IS discipline. Against this backdrop, the present paper seeks to establish the current state of the IS discipline in Australia and New Zealand. Based on a survey of 123 IS researchers, we confirm the sociotechnical nature of the IS discipline in this region, identify key research focus areas, provide research output benchmarks at different academic levels, and assess the level of engagement with general and specialised conferences. Our results provide important insights into the positioning of the IS discipline at the nexus of business and computing-focused research.